Discrete mitochondrial aberrations in the spinal cord of sporadic ALS patients. Issue 8 (6th May 2018) - Delic, Vedad; Kurien, Crupa; Cruz, Josean; Zivkovic, Sandra; Barretta, Jennifer; Thomson, Avery; Hennessey, Daniel; Joseph, Jaheem; Ehrhart, Jared; Willing, Alison E.; Bradshaw, Patrick; Garbuzova‐Davis, Svitlana
Abstract: Amyotrophic lateral sclerosis (ALS) is an adult onset neurodegenerative disease characterized by progressive motor neuron degeneration in the brain and spinal cord leading to muscle atrophy, paralysis, and death. Mitochondrial dysfunction is a major contributor to motor neuron degeneration associated with ALS progression. Mitochondrial abnormalities have been determined in spinal cords of animal disease models and ALS patients. However, molecular mechanisms leading to mitochondrial dysfunction in sporadic ALS (sALS) patients remain unclear. Also, segmental or regional variation in mitochondrial activity in the spinal cord has not been extensively examined in ALS. In our study, the activity of mitochondrial electron transport chain complex IV was examined in post‐mortem gray and white matter of the cervical and lumbar spinal cords from male and female sALS patients and controls. Mitochondrial distribution and density in spinal cord motor neurons, lateral funiculus, and capillaries in gray and white matter were analyzed by immunohistochemistry. Results showed that complex IV activity was significantly decreased only in gray matter in both cervical and lumbar spinal cords from ALS patients. In ALS cervical and lumbar spinal cords, significantly increased mitochondrial density and altered distribution were observed in motor neurons, lateral funiculus, and cervical white matter capillaries. Discrete decreased complex IV activity in addition to changes in mitochondria distribution and density determined in the spinal cord in sALS patients are novel findings. These explicit mitochondrial defects in the spinal cord may contribute to ALS pathogenesis and should be considered in development of therapeutic approaches for this disease. Abstract : The present report demonstrated discrete changes in complex IV activity of post‐mortem spinal cords from sporadic ALS patients. Profoundly, the complex IV deficiency was determined only in gray matter of both cervical and lumbar spinal regions of ALS patients compared to controls.